FILOSOFI GUSJIGANG DALAM DAKWAH PENGEMBANGAN MASYARAKAT ISLAM KUDUS - Bastomi, Hasan (Community Development: Jurnal Pengembangan Masyarakat Islam, 2019)
AbstractGusjigang is an acronym of good (morality), Koran (demanding knowledge) and trade (business), which shows economic stability and at the same time has spiritual maturity. The gusjigang philosophy should be internalized in the implementation of community development da'wah, namely the implementation of da'wah in the Holy community in terms of inviting to do good (yad'uuna ila al-khair), telling people to do good and right or wise (makruf) (wayamuruuna bi al-ma ' ruf) and preventing evil deeds (wayanhauna anilmunkar) should be principled on good practices (morality issues, ahklak), then based on knowledge delivered by preachers who are good at recitation which means studying, diligently worshiping, and then cleverly trading, which invites kindness and prevents munkar can also be through the path of entrepreneurs (entrepreneurs).Keywords:       Philosophy, Gusjigang, Islamic Community Development